Pengaruh Kemandirian Belajar Terhadap Prestasi Belajar Matematika Pada Siswa Kelas VII SMP Negeri 8 Buton - Rahmatia Rahmatia; Mohamad Ikhsan Abu (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2021)
The formulation of the problem in this study was an Effect of Independent Learning on the Mathematics Learning Achievement of VII Grade Students of SMP Negeri 8 Buton. The objective of this research was to see the effect of independent learning on matehematics learning achievement in VII grade student of SMP Negeri 8 Buton. This type of study was a quantitative study with a correlation Ex Post Facto approach. the population in this study were all VII SMP Negeri 8 Buton, which consisted of 5 classes that met 139 student. The sampling technique used was rando, sampling technique, which was selelcted 2 classes from 5 classes randomly. After selecting the sample, namely class VII 2 with a total of 27 students and class VII 3 with a total of 27 students, so that the total sample was 54 students. The data technique in this study used a questionnaire and documention. Based on the results of calculations using simple linear regression linear regression equation: = 108.164 + 0.347 X. With at value of 2.094, significant at 0.041 < 0.05. This indicated that H1 was accepted, or H0 was rejected. This meant that there was a significant influence between independent learning on mathematics learning achievement VII grade students of SMP Negeri 8 Buton.